Confirmation of glufosinate-resistant Palmer amaranth and response to other herbicides. (19th June 2022) - Priess, Grant L; Norsworthy, Jason K; Godara, Navdeep; Mauromoustakos, Andy; Butts, Thomas R; Roberts, Trenton L; Barber, Tom
Abstract: The ability of weed populations to evolve resistance to herbicides affects management strategies and the profitability of crop production. The objective of this research was to screen Palmer amaranth accessions from Arkansas for glufosinate resistance. Additional efforts focused on the effectiveness of various herbicides, across multiple sites of action (SOAs), on each putative-resistant accession. The three putative accessions were selected from 60 Palmer amaranth accessions collected in 2019 and 2020 and screened with to 0.5× and 1× rates of glufosinate. A dose-response experiment was conducted for glufosinate on accessions A2019, A2020, and B2020. The effectiveness of various preemergence- and postemergence-applied herbicides were evaluated on each accession. Resistance ratios of A2019, A2020, and B2020 to glufosinate ranged from 5.1 to 27.4 when comparing LD50 values to two susceptible accessions, thus all three accessions were resistant to glufosinate. All three accessions (A2019, A2020, and B2020) were found to have a reduction equal to or greater than 20 percentage points in mortality to at least one herbicide from five different SOAs equal to or greater than five sites of action. Herbicides from nine different SOAs controlled A2019 at least 20 percentage points less than the susceptible accessions, which points to a need for additional research to characterize the response of this accession.